P3_2 Thick Skin - Acton, Jack; Harding, Ben; Kneebone, Ricky; Harvey, Max (Physics Special Topics, 2017)
We determine the thickness of human skin that would be required to be bulletproof. The kinetic energy of bullets with various calibres are determined and the tensile strength of skin used to find the stopping distance of a bullet inside skin. We find that skin with a thickness of 5-40 cm is required to be bulletproof, dependent on the calibre of the bullet. The limitations of possessing such skin are considered to determine the feasibility of a bulletproof human.